Violation of the 12/23 rule of genomic V(D)J recombination is common in lymphocytes - Parkinson, Nicholas J.; Roddis, Matthew; Ferneyhough, Ben; Zhang, Gang; Marsden, Adam J.; Maslau, Siarhei; Sanchez-Pearson, Yasmin; Barthlott, Thomas; Humphreys, Ian R.; Ladell, Kristin; Price, David A.; Ponting, Chris P.; et al. (Genome Research, 2015)
V(D)J genomic recombination joins single gene segments to encode an extensive repertoire of antigen receptor specificities in T and B lymphocytes. This process initiates with double-stranded breaks adjacent to conserved recombination signal sequences that contain either 12- or 23-nucleotide spacer regions. Only recombination between signal sequences with unequal spacers results in productive coding genes, a phenomenon known as the “12/23 rule.” Here we present two novel genomic tools that allow the capture and analysis of immune locus rearrangements from whole thymic and splenic tissues using second-generation sequencing. Further, we provide strong evidence that the 12/23 rule of genomic recombination is frequently violated under physiological conditions, resulting in unanticipated hybrid recombinations in ∼10% of Tcra excision circles. Hence, we demonstrate that strict adherence to the 12/23 rule is intrinsic neither to recombination signal sequences nor to the catalytic process of recombination and propose that nonclassical excision circles are liberated during the formation of antigen receptor diversity.
10.1101/gr.179770.114